Parental Perspectives on Children's Functional Experiences After Limb Fracture: A Qualitative Study. Issue 2 (February 2022) - Golden-Plotnik, Stevi; Ali, Samina; Moir, Mackenzie; Drendel, Amy L.; Poonai, Naveen; van Manen, Michael
Abstract : Background: Fractures are a common childhood injury. Although the pain associated with fractures is well described, the related functional impact is less understood. When a child's function is impaired, his or her ability to participate in day-to-day life is restricted. Eighty percent of children with fractures experience compromise in daily function. An in-depth understanding of function can guide emergency department (ED) providers' discharge instructions. Objectives: Our aim was to report caregivers' perspectives of the functional impact of limb fractures on their children's day-to-day life activities. Methods: We performed a qualitative study using interviews of caregivers of children (aged 5 to 11 years) who received care for acute, nonoperative long bone fractures in a pediatric ED. Audio-recorded, semistructured telephone interviews were completed 7 to 14 days after the ED visit. Interviews were primarily open ended, including questions targeting areas of function from existing pediatric fracture literature. Qualitative analysis was completed using content analysis. Results: Twenty-five interviews were included in the final analysis. Most of the children were diagnosed with upper extremity fractures, and most participants were mothers. All parents reported a change in their child's function. The most commonly affected areas were sleep, activities of daily living, and play. Play was either self-limited by the child or restricted by the parent. Pain was worse in the first days after discharge. Many children struggled emotionally with functional limitations. All children required help from their parents to perform daily tasks; this required adaptive strategies such as planning, changes to household routine, and missed work. Key concerns from parents included regression in the child's independence and fracture healing and complications. Conclusions: Function is universally impaired in young children with fractures, significantly affecting family life after discharge. Discharge conversations with families should include pain management, changes to activities of daily living, family routines and play, and expectations for fracture healing. Abstract : Supplemental digital content is available in the text.